Nutrition and equality: Brazil’s success in reducing stunting among the poorest - Keefe, Meagan (International Food Policy Research Institute, 2016)
RAPID ADVANCES IN economic development and healthcare in Brazil have contributed to significant improvements in child health and nutrition in recent decades. Brazil met Millennium Development Goal 1—halving the proportion of people whose income is less than $1 a day and halving the proportion of people who suffer from hunger, and Goal 4—reducing by two-thirds the under-five mortality rate. Beyond significant advances in reducing poverty and improving food and nutrition security throughout the country, Brazil has also been successful in reducing socioeconomic inequality in malnutrition. What lies behind this success? This case study examines the policies, approaches, and process that contributed to the reduction in child stunting and other key indicators of malnutrition.